A conceptual framework to enhance students’ experience in dormitories through space optimization and cultural integration - Xiao Wen Tong; Mi Jeong Kim (Journal of Asian Architecture and Building Engineering)
International exchanges have increased following globalization. However, many universities fail to effectively promote intercultural communication between domestic and international students, resulting in cultural segregation. To address this issue, this study explores the dormitory environment and the cultural interaction among students from different cultural backgrounds in Korea. Results from a survey of domestic and international students living in the same dormitory environment showed that the dormitory management system does not fully reflect their perspectives. By exploring four key dimensions – “Habitability,” “Connectivity,” “Sociality,” and “Cultural Integration” – this study found that flexible and comfortable physical spaces improve students’ quality of life substantially. Further, local students’ satisfaction with self-management and self-expression was low. Foreign students relied more on online social networks, but their participation in physical and cultural interactions was lower than expected. This study recommends that differences be transcended in dormitory design and a comprehensive autonomy management model that has cultural interests as the core be built, which would promote social interaction and cultural integration among students.